2009
DOI: 10.1099/mic.0.031005-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional upregulation of four genes of the lysine biosynthetic pathway by homocitrate accumulation in Penicillium chrysogenum: homocitrate as a sensor of lysine-pathway distress

Abstract: The lysine biosynthetic pathway has to supply large amounts of α-aminoadipic acid for penicillin biosynthesis in Penicillium chrysogenum. In this study, we have characterized the P. chrysogenum L2 mutant, a lysine auxotroph that shows highly increased expression of several lysine biosynthesis genes (lys1, lys2, lys3, lys7). The L2 mutant was found to be deficient in homoaconitase activity since it was complemented by the Aspergillus nidulans lysF gene. We have cloned a gene (named lys3) that complements the L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This work found that lysine content increased by nearly 13% under optimal citric acid induction conditions, with the gene expression levels of hcs , hac, and hah being 2.67, 1.97, and 1.90 times higher than the control, respectively. Citric acid induction creates more metabolic flux into lysine biosynthesis, along with upregulating lysine-biosynthesis-related enzymes, and thus significantly increases the lysine content in F. filiformis , which is in line with previous studies proving that synthetic substrate accumulation accelerates biosynthesis pathways [ 30 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This work found that lysine content increased by nearly 13% under optimal citric acid induction conditions, with the gene expression levels of hcs , hac, and hah being 2.67, 1.97, and 1.90 times higher than the control, respectively. Citric acid induction creates more metabolic flux into lysine biosynthesis, along with upregulating lysine-biosynthesis-related enzymes, and thus significantly increases the lysine content in F. filiformis , which is in line with previous studies proving that synthetic substrate accumulation accelerates biosynthesis pathways [ 30 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…In S. cerevisiae , the α-aminoadipate pathway is initiated by homocitrate synthase, which catalyzes the first and rate-limiting step in the pathway and is highly regulated to conserve the use of resources [ 17 ]. Teves et al found that homocitrate was a regulatory substance controlling the lysine biosynthesis pathway by mutating the homoaconitase of Penicillium chrysogenum to achieve a significant accumulation of intracellular homocitrate, which caused a significant increase in the expression of lysine-biosynthesis-related genes, whereas the genes were normally expressed in a lysine auxotroph defective in the homocitrate synthase or in another strain disrupted in the α-aminoadipate reductase [ 30 ]. O’Doherty et al exposed a saccharopine dehydrogenase gene mutant (lys1Δ) strain of S. cerevisiae to lipid oxidant-linoleic acid hydroperoxide (LoaOOH) using a medium containing sufficient lysine, finding that it grew significantly slower compared to the wild-type BY4743 strain [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this homoaconitase performs both reactions that are required for the isomerization has not been convincingly shown. Investigations on homoaconitase mutants from the filamentous fungi Aspergillus nidulans and Penicillium chrysogenum revealed an accumulation of homocitrate, but not homoaconitate (Weidner et al ., ; Teves et al ., ). Thus, it was assumed that homoaconitases from filamentous fungi catalyse both reactions.…”
Section: Introductionmentioning
confidence: 97%
“…A lysine biosynthesis branching intermediate α-aminoadipic acid is also one of the the precursors of the δ-L-α-aminoadipyl-L-cysteinyl-D-valine (ACV) tripeptide in the synthesis of penicillin (Esmahan et al, 1994). Indeed, one study found that penicillin production was impaired in P. chrysogenum mutants in which the branching point of the lysine biosynthesis pathway was blocked due to unavailability of α-aminoadipic acid (Teves et al, 2009), while another found that disruption of the lys2 gene led to penicillin overproduction due to an increased pool of α-aminoadipic acid (Casqueiro et al,. 1999).…”
Section: Introductionmentioning
confidence: 99%